A shift towards self-transcendence: can service learning make a difference?. Issue 1 (11th March 2019) - Petrovskaya, Irina
Abstract : Purpose: This paper aims to answer a question whether a course that combines in-class teaching and the out-class elements of service learning can shift students' values from self-enhancement to self-transcendence. Design/methodology/approach: The study employed a pre-test-post-test control group research design. Two groups of the first year undergraduate business students who took the course served as the experimental groups (N = 79), and two groups of the second year students served as the control groups (N = 73). Schwartz's Portrait Values Questionnaire (PVQ-40) was used to measure values, and a t -test was applied to compare value scores at the beginning and the end of the course. Findings: A statistically significant value change toward self-transcendence was found in one of the two experimental groups, and no change was registered in the control groups. Analysis of the course activities and participation suggests that the change was brought about by the variations in the volunteering experiences. Originality/value: This study contributes to the research that focuses on the outcomes of service learning. The research on how service learning affects values, especially pro-social ones, is currently limited. The present study suggests implications for further research and discussion on the possible ways to promote the values of self-transcendence through educational activities.